Toward the development of podocyte-specific drugs - Reiser, Jochen (2010)
Most kidney diseases that ultimately lead to end-stage renal failure originate within the glomerulus and are associated with proteinuria. Treatment options are unspecific and offer partial cures at best because available therapies do not primarily treat glomerular cells but rather act systemically and thus cause many side effects. Most glomerulopathies directly stem from injury to podocytes, cells that have a key role in the maintenance of the glomerular filter. Thus, these cells constitute an obvious and promising target for the development of novel kidney-protective drugs. During the last decade, enormous advances have been made in the understanding of podocyte structure and function. A number of pathways that are altered during glomerular diseases may be targeted by novel small- and large-molecule drugs as well as biologicals that have been identified in nephrology and other areas of drug development. Cultured podocytes provide a valuable model for high-throughput drug screening assays. Furthermore, podocytes have been shown to possess many features that make them particularly good target cells for renal protection. This mini-review discusses some of the most recent promising data related to potential drug therapy for proteinuria and kidney disease through direct podocyte targeting.